Isotopic and spectral signatures unravel the sources, preservation and degradation of sedimentary organic matter in the Dongzhai Harbor mangrove estuary, southern China - Yan, Lu; Xie, Xianjun; Heiss, James W.; Peng, Kang; Deng, Yamin; Gan, Yiqun; Li, Qinghua; Zhang, Yanpeng (Journal of hydrology (Amsterdam), 2023)
[Display omitted] •Spatial patterns of SOM apportionment are identified by 13C and 15N isotopes.•The feature of SOM and biogenic elements vary along estuarine salinity gradient.•Clay, biodeposits, Fe/Mn minerals and redox constrain SOM burial and degradation.•Mangrove wetland environments are affected by SOM biogeochemical processes. Sedimentary organic matter (SOM) production and transformation processes have a prominent role in regulating biogenic element cycling in mangrove ecosystems. However, aquaculture biodeposits can substantially affect source apportionments and biogeochemical processes of SOM within mangroves. In this study, natural stable isotopes (13C and 15N), spectral techniques, and hydrogeochemical analysis were used to elucidate the sources, preservation, and degradation of SOM across the Dongzhai Harbor (DZH) estuary, southern China, where aquaculture systems are extensive. Along the estuarine salinity gradient, sediment and bottom water samples were collected from the upper fluvial mangrove zones to the lower marine endmember. Results indicated that source contributions to SOM along the estuarine gradient were spatially heterogeneous. Aquaculture-derived organic matter was the largest contributor to the Sanjiang River (44.29 %) in the upper estuary, and terrestrial sources from C3 mangrove forests were highest in the Yanfeng East River (62.87 %) near the middle estuary. Farther seaward, marine plankton sources were elevated in the Dongzhai Harbor channel (64.15 %) and Yanfeng West River (48.83 %) of the lower estuary. The terrestrial/microbial humic-like component (C1), tryptophan-like component (C2), and soil-derived fulvic acid (C3) were identified from the samples using fluorescence excitation emission matrices and parallel factor analysis (EEM-PARAFAC). Results show that in the upper and middle estuary, SOM was preserved by sedimentation due to the abundance of fine-grained aquaculture-derived biodeposits, weak hydrodynamic conditions, and the formation of Fe/Mn-humus complexes. In contrast, in the lower estuary, SOM originated from marine plankton and was rapidly degraded via aerobic respiration. Moreover, correlations between δ13C and δ15N values vs C/N ratios further suggest progressive SOM degradation from initial diagenesis to post-depositional geochemical processes. This study provides new insights into aquacultural and environmental factors controlling SOM preservation and degradation within estuaries. The findings have implications for shoreline stability and the protection and restoration of estuarine mangrove wetlands.